Ð¥Ñ–Ð¼Ð°Ð·Ð°, Ñ‚Ð¾Ð½Ñ–Ð½ Ñ‚Ð° ÐºÐ°Ð»ÑŒÐ¿Ð°Ñ—Ð½Ð¸ Ð·Ð° ÑƒÐ¼Ð¾Ð² ÑˆÑ‚ÑƒÑ‡Ð½Ð¾Ð³Ð¾ Ð³Ñ–Ð¿Ð¾Ð¼ÐµÑ‚Ð°Ð±Ð¾Ð»Ñ–Ñ‡Ð½Ð¾Ð³Ð¾ ÑÑ‚Ð°Ð½Ñƒ Ñƒ Ñ…Ð¾Ð¼â€™ÑÐºÑ–Ð² - Samokhina, L. M.; Lomako, V. V.; Shilo, A. V. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2007)
The activity of enzymes of alternative ways of angiotensin II formation (chymase, tonin) and calcium-dependent proteinases (calpains) in hamsters serum, nuclear-free fractions of tissue gomogenates of cerebral cortex, brain stem, hypothalamus, cerebellum, lung, heart, liver and kidneys under artificial hypometabolic state (AHMS) (Andjus-Bakhmetev-Giaja method) with enzymatic (10–9–10–10 g) method have been studied. It has been shown that lung, heart, liver, kidneys and brain structures, which are critical for vital function were the most susceptible to AHMS development and at the self-rewarming stage. Increased chymase activity in liver and kidneys on the background of decreased tonin activity and elevated calpains activity may indicate vasoconstriction development and stimulation of cell and tissue damage, correspondingly. All the changes found were mainly normalized after 24 h.